Limitations on the Office of the President in Indonesia from a Legal Theory Perspective - Asmariah, Asmariah (LPPM Universitas Primagraha, 2021)
This study uses a normative juridical approach, which is to approach the problem based on legal principles or norms that are the object of discussion. This study aims to find out whether the applicable law that is stipulated and applied is unilateral by and/or only for the interests of the authorities. The issue of the President of the three periods in terms of the legal aspect is whether it only guarantees the interests of a few people in power or guarantees the interests of justice for everyone, and how the principles of the rule of law apply whether absolute rechtsstaat or democratische rechtsstaat. Limiting the President's term of office is important because if it is not limited it will open up the possibility of abuse of authority and the emergence of authoritarianism in a country. It can be seen from all countries that use a Presidential Government system, almost all of them use term limits on presidential candidates in each country. To avoid the occurrence of Abuse of power, you can use the concept of No re-election and Only one re-election which is the right step to minimize the possibility of abuse of authority.